2020
DOI: 10.3389/fmars.2020.00630
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018

Abstract: Anthropogenic contaminants in the marine environment often biodegrade slowly, bioaccumulate in organisms, and can have deleterious effects on wildlife immunity, health, reproduction, and development. In this study, we evaluated tissue toxicant concentrations and pathology data from 83 odontocetes that stranded in the southeastern United States during 2012-2018. Mass spectrometry was used to analyze blubber samples for five organic toxicants (atrazine, bisphenol-A, diethyl phthalates, nonylphenol monoethoxylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…In our study, BPA concentrations ranged from 4.16 to 166 ng g –1 dw, which were in the same order of magnitude as the levels in dolphins from the Macaronesian region, North Atlantic Ocean . However, the highest BPA concentration from this study was much lower than the top level of BPA (397.4 μg g –1 dw) reported in the blubber samples from stranded white-beaked dolphins (Lagenorhynchus albirostris) in the southeastern United States …”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…In our study, BPA concentrations ranged from 4.16 to 166 ng g –1 dw, which were in the same order of magnitude as the levels in dolphins from the Macaronesian region, North Atlantic Ocean . However, the highest BPA concentration from this study was much lower than the top level of BPA (397.4 μg g –1 dw) reported in the blubber samples from stranded white-beaked dolphins (Lagenorhynchus albirostris) in the southeastern United States …”
Section: Resultssupporting
confidence: 46%
“…35 However, the highest BPA concentration from this study was much lower than the top level of BPA (397.4 μg g −1 dw) reported in the blubber samples from stranded white-beaked dolphins (Lagenorhynchus albirostris) in the southeastern United States. 34 3.2. Temporal Trends of Bisphenols in Juveniles and Adults.…”
Section: Bisphenol Levels and Their Variations Related Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cyanotoxins, anthropogenic contaminates (ACs) generated by agricultural and industrial processes can persist in the aquatic environment, are poorly metabolized, and can cause toxicity. ACs are potential threats to dolphins and other marine mammals [ 18 ]. ACs such as methylmercury (MeHg), a potent neurotoxicant, can also biomagnify in the marine food web and concentrate in the brain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The asexual stage of T. gondii begins after the ingestion of oocysts or the tissue cysts ( Figure 5 ). Studies demonstrated that the toxoplasmosis lesions in cetaceans were non-suppurative meningoencephalitis and choroiditis, lymphoplasmacytic perivascular cuffs, gliosis, neuronal degeneration, necrosis, abortion, and may lead to a decline in health, contributing to stranding and mortality events [ 25 , 35 , 36 , 37 ]. Reproduction and population health effects can be huge for threatened populations.…”
Section: Introductionmentioning
confidence: 99%